Reproducibility of pulmonary blood flow measurements by phase-contrast MRI using different 1.5 T MR scanners at two institutions. (January 2017) - Iraha, Rin; Tsuchiya, Nanae; Yamashiro, Tsuneo; Iwasawa, Tae; Murayama, Sadayuki
Background: Magnetic resonance imaging (MRI) can be beneficial for diagnosis of disease by offering quantitative information. However, reproducibility can be a major problem when there is a numerical threshold in multi-institution, multi-vendor situations. Purpose: To measure pulmonary blood flow with phase-contrast (PC) imaging using two different MR scanners (1.5 T) at different institutions in the same participants and to examine the reproducibility of the measurements. Material and Methods: Participants were 10 healthy volunteers (5 men; age range, 27–36 years). The measurements included the mean and maximal blood velocities, the mean blood flow volume, and the acceleration time and volume (AT and AV), derived from the time-flow curve of the PC-MRI. Simultaneously obtained maximal, minimal, and mean areas from regions of interest set in the pulmonary artery were also calculated. In order to calculate the reproducibility of the quantitative variables, intra-class correlation coefficients (ICCs) were employed. When an adequate ICC was obtained, Bland–Altman analysis was conducted to identify any systematic bias. Results: The ICCs were almost perfect for the mean blood flow volume and the AV (r = 0.82 and 0.80), and were substantial in the mean and maximal areas, and the AT (r = 0.63, 0.74, and 0.64, respectively). However, there was a fixed bias in the area measurement between the two scanners. Also, the AV had a proportional bias. Conclusion: Our results reveal that various indices derived from PC-MRI on different MR scanners are promising as common indices for pulmonary flow assessment. Research and clinical use of PC-MRI for the pulmonary artery is expected to extend to multi-institution situations.